Factors Influencing Patient Satisfaction in Private Hospitals: A Study of Age, Gender, Quality of Care, and Communication - Raikhola, Pushkar Singh (NPRC Journal of Multidisciplinary Research, 2025)
Background: Overall, patient satisfaction is one of the important components of healthcare quality. It reflects not only the patient's experience but also the overall effectiveness of healthcare delivery. Quality of care, communication, age, and gender are some of the factors that can influence the level of satisfaction among patients. Understanding these relationships is critical to improve healthcare outcomes and experiences in private hospitals.Objective: This study, therefore, investigates the determinants of patient satisfaction in private hospitals and narrows down to the relationship between quality of care, communication, age, and gender. It examines how these dimensions relate to overall patient satisfaction in identifying areas to be improved in healthcare delivery.Methods: The research design was based on a survey approach, and the sample size consisted of 204 patients from a private hospital. The responses were sought on the quality of care received, communication with health professionals, and overall hospital experience. Data analysis consisted of Pearson correlation, ANOVA, and independent samples t-test for testing relationships between variables.Results: Results indicated that quality of care was associated positively with overall satisfaction, and it also was the case with communication. Regression analysis showed that age significantly affected patients' satisfaction and indeed, this is due to different age groups showing their satisfaction in varying levels. However, gender was not significant enough in determining the satisfaction of patients.Conclusion: The study confirms that, indeed, the quality of care and effective communication are major propellers of the level of patients' satisfaction at private hospitals. While age is influential on shaping satisfaction, gender does not have a major influence on outcomes of satisfaction. These find ings identify the importance of addressing age needs and improving communication to enhance patient experience.Novelty: The study adds to the growth in the literature of patient satisfaction with a view of the distinctive roles of quality of care, communication, age, and gender played in private hospitals. It gives an in-depth analysis of these factors and, as such, offers practical recommendations for healthcare providers.